Grupo educativo e qualidade de vida de idosos hipertensos e diabéticos - Santos, Lúcia Helena Rack dos Santos (2016)
Educational supporting programs can be effective in the control of Arterial Hypertension and Diabetes. They promote the change of attitudes, stimulating self-care and minimizing the action of modifiable risk factors, thus contributing to improve the quality of life and reduction of direct and indirect health costs. Objective: To analyze and compare the quality of life of hypertensive and diabetic elderly patients registered in the HIPERDIA from a school medical health center in the interior of São Paulo that participated in educational groups. Method: Descriptive research of survey type with a structured questionnaire to analyze the quality of life of 264 elderly people of both sexes, with type 2 Diabetes Mellitus and Systemic Arterial Hypertension registered in HIPERDIA, in 2011, who participated in an educational group from 2012 to 2014. A total of 85 individuals with less than 50% frequency to educational action, and 179 individuals with frequency equal or greater than 50%. The WHOQOL-BREF questionnaire was used to assess the quality of life. T test was used for the analysis of the scores. All statistical tests were applied with significance level of 5% (p = 0.05); the software used was Minitab 17 (Minitab Inc.). Results: Predominantly female, white, married, retired, primary level of education, average income between 2 and 5 minimum wages; time of diagnosis from 11 to 20 years, they did not ingest alcoholic beverages; non-smokers . Those who practiced physical activity went walking, had healthy diet. Median age of 71 years. There were no significant differences in the age and number of residents between the groups. For individuals with a frequency lower than 50%, the social domain followed by the environmental and general domains presented problems regarding compliance to the instrument of quality of life. Conclusion: Quality of life remained the same in both groups. The educational group is an important strategy for the control of Diabetes and Hypertension and, consequently, this can help on the quality of life. However, it is necessary to readjust its structure with directed and planned attention to the target public, strengthening the link between the team and the user, providing greater compliance and continuity of actions.